Electrode coating material screening method, electrode material, secondary battery
The calculation of screening electrode coating materials through density functional theory solves the problem of low screening efficiency of electrode coating materials in the prior art, and realizes the interface modification of electrode materials and the performance improvement of secondary battery.
Patent Information
- Application Number
- CN202111137464.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2041-09-27
AI Technical Summary
In the prior art, the screening method of electrode coating material requires assembly into a whole battery for electrochemical properties testing, which is inefficient and cumbersome, so it is impossible to accurately predict the effect of coating material.
Through density functional theory, the surface energy, formation energy and lithium ion migration rate of electrode active materials and coating materials were calculated, and the coating materials with high lithium ion migration efficiency and low reactivity with the electrolyte were screened out, and a data screening model was constructed to quickly Accurately screen the electrode coating material.
It realizes rapid and accurate screening of interface modification of electrode materials, improves the electrochemical performance of electrode active materials, and extends the cycle life and energy density of secondary batteries.
Smart Images

Figure CN113937263B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and in particular relates to a method for screening electrode coating materials, an electrode material, and a secondary battery. Background Art
[0002] With the development of new energy vehicles, the development of new lithium-ion batteries with higher energy density, more economical price and longer life has become a key research content in the field of electrochemical energy storage in my country. Since the positive electrode is the donor of ions in secondary batteries, it also determines the energy density and comprehensive electrochemical performance of the battery. The development of high-energy-density lithium-ion battery positive electrode materials has become a research hotspot in academia and industry. Among them, high-nickel ternary positive electrode materials have attracted much attention due to their excellent properties such as high voltage and high energy density, and products have also been developed in series. Although ternary positive electrode materials have excellent electrochemical properties, during the use of batteries, lithium-ion battery positive electrode materials will have a certain capacity decay. The main reasons include positive electrode / electrolyte interface side reactions, lithium dendrite formation, etc.
[0003] In order to improve the cycle life and safety of batteries, researchers have proposed positive electrode surface coating and interface doping. The current effective method is to coat the surface of the positive electrode material with a layer of material to avoid direct contact between the positive electrode surface and the electrolyte, or to dope the surface elements to passivate the high active sites on the surface and inhibit the chemical reaction with the interface electrolyte. 0.50 Mn 0.30 Ni 0.20 O2 (NCM532) surface coated with Li2TiO2 rock salt structure oxide, can be well attached to the surface of NCM532, inhibiting the positive electrode / electrolyte interface reaction; NCM71515 positive electrode surface coated with Li2ZrO3 can effectively protect the positive electrode structure and promote lithium ion transport, etc. However, the current positive electrode surface coating materials are still in the "trial and error" stage. After selecting a positive electrode coating material and preparing the core-shell structure of the positive electrode coating material, it is necessary to assemble it into a full battery for electrochemical property testing to verify the effect of the coating material. This type of experimental method is inefficient and the procedure is cumbersome. How to accurately predict the coating material for screening is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present application is to provide a method for screening electrode coating materials, an electrode material, and a secondary battery, aiming to solve to a certain extent the problem that the screening method of electrode coating materials needs to be assembled into a full battery for electrochemical performance testing to verify the effect of the coating material, which is inefficient and has cumbersome procedures.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a method for screening electrode coating materials, comprising the following steps:
[0007] Obtaining an electrode active material, calculating the surface energy of different crystal faces of the electrode active material by density functional theory, and determining the interface structure of the electrode active material;
[0008] Obtaining a coating material, calculating the surface energy of the coating material by density functional theory, and determining an interface system of the coating material;
[0009] Based on the interface structure of the electrode active material and the interface system of the coating material, calculating the formation energy of the electrode active material and the coating material, and determining the formation energy system of the coating material;
[0010] Based on the formation energy system of the coating material, the migration rate of lithium ions is calculated by density functional theory to determine the migration system of the coating material;
[0011] Based on the formation energy system of the coating material, the reaction barrier and reaction thermodynamics of the coating material and the electrolyte are calculated by density functional theory to determine the reaction kinetic system of the coating material;
[0012] Based on the migration system of the coating material and the reaction kinetics system of the coating material, the electrode coating material is screened and obtained.
[0013] In a second aspect, the present application provides an electrode material having a core-shell structure, comprising an inner core of an electrode active material and a shell layer coated on the outer surface of the inner core, wherein the electrode coating material of the shell layer is screened by the above-mentioned electrode coating material screening method.
[0014] In a third aspect, the present application provides a secondary battery, characterized in that the secondary battery contains the above-mentioned electrode material.
[0015] The first aspect of the present application provides a method for screening electrode coating materials. The surface energy of different crystal planes of electrode active materials is calculated by density functional theory, the stability of the surface structure of electrode active materials is investigated, and the crystal plane with stable surface structure is used as the interface structure of electrode active materials; at the same time, the surface energy of coating materials is calculated, and coating materials with stable surface structure are screened as the interface system of coating materials. By calculating the surface energy separately, electrode active materials and coating materials that are easy to combine are preliminarily screened. The formation energy of electrode active materials and coating materials is further calculated based on the materials screened by surface energy, and coating materials with stable structure after composite with electrode active materials are screened to determine the formation energy system of coating materials, that is, to construct a coating material stability database. Then, for the materials in the formation energy system of coating materials, the migration efficiency of lithium ions is calculated separately, and coating materials with high lithium ion migration efficiency are screened; at the same time, the reaction kinetic parameters such as reaction barrier and reaction thermodynamics between materials and electrolytes in the formation energy system of coating materials are calculated, and coating materials with low reactivity with electrolytes are screened. Finally, based on the migration system of the coating material and the reaction kinetics system of the coating material, the coating material with high lithium ion migration efficiency and low reaction activity with the electrolyte is screened as the electrode coating material, which is conducive to obtaining electrode materials with excellent comprehensive performance. The electrode coating material screening method of this application constructs a data screening model based on the interface microstructure level. Through high-throughput calculation, the best coating material on the surface of the electrode active material can be quickly and accurately screened, thereby accurately modifying the interface of the electrode active material, improving the electrochemical performance of the electrode active material, and laying a good foundation for improving the performance of secondary batteries.
[0016] The electrode material provided in the second aspect of the present application has a core-shell structure, and its coating material is screened by the above method, so that the electrode material not only has a higher capacity, but also has good structural stability during the cyclic charge and discharge process, low reaction activity with the electrolyte, few side reactions, and a long cycle life.
[0017] The secondary battery provided in the third aspect of the present application contains the above-mentioned electrode material, which has a high capacity, and during the cyclic charge and discharge process, the electrode material has good structural stability, low reaction activity with the electrolyte, and few side reactions; thereby improving the secondary battery's energy density, cycle stability, cycle life and other electrochemical comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0019] Figure 1 It is a schematic flow chart of the electrode coating material screening method provided in an embodiment of the present application. DETAILED DESCRIPTION
[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0022] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple.
[0023] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0025] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass in the embodiment description of the present application can be μg, mg, g, kg and other mass units known in the chemical industry.
[0026] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0027] A first aspect of an embodiment of the present application provides a method for screening an electrode coating material, comprising the following steps:
[0028] S10. Obtaining electrode active materials, calculating the surface energy of different crystal faces of the electrode active materials by density functional theory, and determining the interface structure of the electrode active materials;
[0029] S20. Obtaining a coating material, calculating the surface energy of the coating material by density functional theory, and determining an interface system of the coating material;
[0030] S30. Based on the interface structure of the electrode active material and the interface system of the coating material, calculating the formation energy of the electrode active material and the coating material, and determining the formation energy system of the coating material;
[0031] S40. Based on the formation energy system of the coating material, the migration rate of lithium ions is calculated by density functional theory to determine the migration system of the coating material;
[0032] S50. Based on the formation energy system of the coating material, the reaction barrier and reaction thermodynamics of the coating material and the electrolyte are calculated by density functional theory to determine the reaction kinetic system of the coating material;
[0033] S60. Based on the migration system of the coating material and the reaction kinetic system of the coating material, the electrode coating material is screened and obtained.
[0034] The first aspect of the present application embodiment provides a method for screening electrode coating materials. The surface energy of different crystal planes of electrode active materials is calculated by density functional theory, the stability of the surface structure of electrode active materials is investigated, and the crystal plane with stable surface structure is used as the interface structure of electrode active materials; at the same time, the surface energy of coating materials is calculated, and coating materials with stable surface structure are screened as the interface system of coating materials. By calculating the surface energy separately, electrode active materials and coating materials that are easy to combine are preliminarily screened. The formation energy of electrode active materials and coating materials is further calculated based on the materials screened by surface energy, and coating materials with stable structure after composite with electrode active materials are screened to determine the formation energy system of coating materials, that is, to construct a coating material stability database. Then, for the materials in the formation energy system of coating materials, the migration efficiency of lithium ions is calculated respectively, and coating materials with high lithium ion migration efficiency are screened; at the same time, the reaction kinetic parameters such as reaction barrier and reaction thermodynamics between materials and electrolytes in the formation energy system of coating materials are calculated, and coating materials with low reactivity with electrolytes are screened. Finally, based on the migration system of the coating material and the reaction kinetics system of the coating material, the coating material with high lithium ion migration efficiency and low reactivity with the electrolyte is screened as the electrode coating material, which is conducive to obtaining electrode materials with excellent comprehensive performance. The electrode coating material screening method of the embodiment of the present application constructs a data screening model based on the interface microstructure level. Through high-throughput calculation, the optimal coating material on the surface of the electrode active material can be quickly and accurately screened, thereby accurately modifying the interface of the electrode active material, improving the electrochemical performance of the electrode active material, and laying a good foundation for improving the performance of secondary batteries.
[0035] In some embodiments, in the above step S10, the electrode active material can be either a positive electrode active material or a negative electrode active material. The electrode coating material screening method of the present application embodiment is applicable to any electrode active material that needs to be coated. It is particularly suitable for highly active positive electrode materials, such as ternary positive electrode materials, etc. These highly active positive electrode materials are prone to transition metal dissolution, side reactions with electrolytes, and formation of lithium dendrites during the battery cycle charge and discharge process. The electrode coating material screening method of the present application embodiment can quickly, accurately and efficiently screen out the best coating materials for highly active positive electrode materials such as ternary positive electrode materials.
[0036] In some embodiments, the step of calculating the surface energy of different crystal faces of the electrode active material includes: performing a surface treatment on the electrode active material to construct different crystal faces, and calculating the surface energy of different crystal faces by the formula: γ1 = (E slab -NE bulk ) / 2A calculates the surface energy γ1 of different crystal planes; where E slab is the surface system energy of the electrode active material, E bulkis the bulk structure energy of the electrode active material, N is the number of atoms in the surface system of the electrode active material, and A is the surface area of the surface system of the electrode active material. The present application embodiment calculates the surface energy of different crystal faces of the electrode active material to investigate the stability of the surface structure of the electrode active material. The smaller the surface energy, the larger the corresponding crystal face, the more stable the constructed surface structure, and the more conducive it is to combine with the coating material to form a core-shell structure composite electrode material with stable performance.
[0037] In some embodiments, the step of determining the interface structure of the electrode active material comprises: screening The crystal plane of the present application is used as the interface structure of the electrode active material. The embodiment of the present application selects a crystal plane with low surface energy as the interface structure of the electrode active material. The selected crystal plane is large and has good surface structure stability, which is conducive to combining with the coating material.
[0038] In some embodiments, in the above step S20, the coating material corresponds to the electrode active material. If the electrode active material is selected from the positive electrode active material, the coating material is selected from the positive electrode coating material matching the positive electrode active material; if the electrode active material is selected from the negative electrode active material, the coating material is selected from the negative electrode coating material matching the negative electrode active material.
[0039] In some embodiments, the positive electrode active material is selected from at least one of: nickel cobalt manganese oxide ternary material, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, and nickel cobalt aluminum oxide. In this case, the positive electrode coating material includes: at least one of: LiTaO3, Li3PO4, LiNbO3, Li2TiO2, Li2ZrO3, and Li2SiO3.
[0040] In some embodiments, the step of calculating the surface energy of the coating material includes: obtaining different coating materials and performing cross-section processing to construct different Miller index surfaces, and using the formula: γ2 = (E' slab -N'.E' bulk ) / 2A' to calculate the surface energy γ2 of different coating materials; where E' slab is the surface system energy of the coating material, E' bulk is the bulk structure energy of the coating material, N' is the number of atoms on the surface system of the coating material, and A' is the surface area of the surface system of the coating material. The present application embodiment calculates the surface energy of different coating materials to examine the structural stability of different coating materials. The smaller the surface energy, the more stable the surface structure, and the more conducive it is to combine with the electrode active material to form a core-shell structure composite electrode material with stable performance.
[0041] In some embodiments, the step of determining the interface system of the coating material comprises: screening As the interface system of the coating material, the coating material with low surface energy has better structural stability and better bonding stability with the electrode active material.
[0042] In some embodiments, in the above step S30, the step of calculating the formation energy of the electrode active material and the coating material includes: based on the interface structure of the electrode active material and the interface system of the coating material, selecting the electrode active material and the coating material, and calculating the formation energy of the electrode active material and the coating material by the formula: f =E(Electrode|shell)-E(Electrode)- E(shell) Calculate the structure formation energy E between the selected electrode active material and the coating material f ; Wherein, E(Electrode|shell) is the surface system energy of the electrode active material and the coating material to form a core-shell structure, E(Electrode) is the surface system energy of the electrode active material to form an electrode, and E(shell) is the surface system energy of the coating material to form a shell layer. E(Electrode|shell), E(Electrode), and E(shell) can be calculated by density functional theory (DFT) respectively. The embodiment of the present application calculates the surface energy of the electrode active material and the coating material respectively, and after preliminarily screening out the electrode active material crystal plane and the coating material that are easy to combine, further calculates the formation energy of the electrode active material and the coating material, and takes the size of the interface formation energy as a variable. The lower the formation energy, the easier it is for the electrode active material and the coating material to combine, and the higher the structural stability, thereby screening out the coating material with low formation energy with the electrode active material, screening out the coating material with large formation energy, and constructing the formation energy system of the coating material by further screening the coating material.
[0043] In some embodiments, the step of determining the formation energy system of the coating material includes: screening coating materials with surface formation energy lower than 0.8 eV as the formation energy system of the coating material. Coating materials with such formation energy are more easily combined with electrode active materials and have better structural stability.
[0044] In some embodiments, in the above step S40, the step of calculating the lithium ion migration rate includes:
[0045] S41. Select the coating material from the formation energy system of the coating material, through the formula: E a =E 过渡态 -E 初始态 Calculate the migration energy barrier E of lithium ions from the shell of the coating material to the core of the active material a , where E 过渡态 is the energy corresponding to the transition state structure, E 初始态 The architectural energy for lithium ions not embedded in active materials;
[0046] S42. By formula: r = A" exp (-E a / kT) to calculate the lithium ion migration rate r; where A” is the pre-factor, E a is the migration energy barrier, k is the Boltzmann constant, and T is the temperature.
[0047] The present embodiment further selects coating materials from the formation energy system of coating materials, and examines the migration energy barrier change E of the entire process of lithium ions migrating from the surface of the coating material shell to the core of the electrode active material. a (E a =E 过渡态 -E 初始态 ), and then through r = A" exp(-E a / kT) to calculate the lithium ion migration efficiency, study the lithium insertion kinetics of different coating materials in the formation energy system of the coating material, further screen out the coating materials with high lithium ion migration efficiency and low migration barrier, and determine the migration system of the coating material. In addition, the thermodynamic changes of the whole process of lithium ion migration from the surface of the coating material shell to the core of the electrode active material can also be examined. b (E b =E 末态 -E 初始态 ), and the lithium ion migration process is thermodynamically favorable through thermodynamic changes. The thermodynamic change E b The more negative the value, the more favorable it is for lithium ion migration. 末态 、E 初始态 The corresponding architecture is obtained by density functional theory DFT calculation, E 过渡态 -E 初始态 It can be obtained by the Nudgedelastic band (NEB) method.
[0048] In some embodiments, the step of determining the migration system of the coating material includes: screening a coating material with a lithium ion migration energy barrier not higher than 0.4 eV as the migration system of the coating material, that is, in the migration system of the coating material, the lithium ion migration barrier of the coating material is <0.4 eV, and a low migration energy barrier corresponds to a high lithium ion migration efficiency, so the coating material not higher than 0.4 eV ensures that the lithium ions have a high migration efficiency. The coating material screened in the embodiment of the present application has high lithium ion migration efficiency and low migration barrier.
[0049] In some embodiments, in the above step S50, based on the formation energy system of the coating material, the reaction barrier and reaction thermodynamics of the coating material and the electrolyte are calculated by density functional theory. The larger the reaction barrier, the more positive the thermodynamics, the more inert the reaction between the coating material and the electrolyte, and the more stable the composite electrode material formed by the coating material and the electrode active material during the battery charge and discharge cycle.
[0050] In some embodiments, the step of determining the reaction kinetic system of the coating material includes: screening a coating material whose reaction barrier with the electrolyte is not less than 0.7 eV and whose thermodynamics of reaction with the electrolyte is greater than 0 eV as the reaction kinetic system of the coating material. The coating material screened in the embodiment of the present application has low electrolyte reactivity and good stability.
[0051] In some embodiments, in the above step S60, the step of screening the electrode coating material includes: selecting a coating material that satisfies both the migration system of the coating material and the reaction kinetic system of the coating material as the electrode coating material. Based on the migration system of the coating material and the reaction kinetic system of the coating material, the embodiment of the present application finally screens out a highly stable electrode coating material with little effect on lithium insertion kinetics and low interfacial electrolyte reactivity.
[0052] The present application embodiment screens out coating materials with high stability, i.e., low formation energy, through the above-mentioned embodiment steps, which are easy to combine with the electrode active material and have good stability, which is conducive to the preliminary determination of the electrode active material / coating material composite stable structure. In order to further ensure the comprehensive electrochemical performance of the core-shell structure composite electrode material, the present application embodiment further studies the lithium insertion kinetics and electrolyte reaction kinetics on the basis of the coating interface, and screens the coating materials that can simultaneously meet the requirements of small effect on lithium insertion kinetics and low interfacial electrolyte reaction activity, so as to achieve accurate screening of the coating structure and the coating material, so that the electrode active material / coating material core-shell structure composite electrode material has the best electrochemical comprehensive performance.
[0053] A second aspect of an embodiment of the present application provides an electrode material. The electrode material is a core-shell structure, including an electrode active material core and a shell layer coated on the outer surface of the core. The electrode coating material of the shell layer is screened by the above-mentioned electrode coating material screening method.
[0054] The electrode material provided in the second aspect of the embodiment of the present application has a core-shell structure, and its coating material is screened by the method of the above embodiment, so that the electrode material not only has a higher capacity, but also has good structural stability during the cyclic charge and discharge process, low reaction activity with the electrolyte, few side reactions, and a long cycle life.
[0055] A third aspect of the embodiments of the present application provides a secondary battery comprising the above-mentioned electrode material.
[0056] The secondary battery provided in the third aspect of the embodiment of the present application contains the above-mentioned electrode material, which has a higher capacity. In addition, during the cyclic charge and discharge process, the electrode material has good structural stability, low reaction activity with the electrolyte, and few side reactions; thereby improving the secondary battery's comprehensive electrochemical performance such as energy density, cycle stability, and cycle life.
[0057] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in performance of the electrode coating material screening method, electrode material and secondary battery in the embodiments of the present application, the above technical scheme is illustrated by multiple embodiments below.
[0058] Example 1
[0059] A method for screening electrode coating materials comprises the steps of:
[0060] ① Construct the (100), (001), (110), (104) and other crystal planes on different surfaces of the NCM811 positive electrode, calculate the surface energy of each crystal plane, and select the (104) crystal plane with a surface energy of 0.49 eV as the interface structure of the NCM811 positive electrode material. The surface energy (γ1) calculation formula is as follows: γ1 = (E slab -NE bulk ) / 2A calculates the surface energy γ1 of different crystal planes; where E slab is the surface system energy of NCM811 cathode material, E bulk is the bulk structure energy of NCM811 cathode material, N is the number of atoms in the surface system of NCM811 cathode material, and A is the surface area of the surface system of NCM811 cathode material.
[0061] ②Systematically select a series of coating materials, such as LiTaO3, Li3PO4, LiNbO3, Li2TiO2, Li2ZrO3, Li2SiO3, etc., construct different surfaces of the coating materials such as (100), (012) and (110) crystal planes, calculate the surface energy, and select the surface energy The surface and surface energy of the material LiNbO3(012) are The surface of the material Li3PO4 (100) is used to construct the interface system database of the coating material. The surface energy (γ2) is calculated as follows: γ2 = (E' slab -N'.E' bulk ) / 2A' to calculate the surface energy γ2 of different coating materials; where E' slab is the surface system energy of the coating material, E' bulk is the bulk structure energy of the coating material, N' is the number of atoms in the surface system of the coating material, and A' is the surface area of the surface system of the coating material.
[0062] ③ Study the coating effect between the coating material and the NCM811 positive electrode material, and calculate the structure formation energy (E f=E(cathode|shell)-E(cathode)-E(shell)). E(cathode|shell), E(cathode) and E(shell) can be obtained by density functional theory (DFT) calculation of cathode|shell core-shell system, cathode surface system and shell surface system, respectively. Taking the interface formation energy as a variable, NCM811 / LiNbO3 materials and NCM811 / Li3PO4 materials with formation energy lower than 0.8eV were screened out, and a formation energy system database of coating materials was constructed.
[0063] ④ Conduct theoretical research on lithium insertion in the formation energy system database of the screened coating materials. Investigate the thermodynamic changes (final state energy - initial state energy) and migration energy barrier changes (transition state energy - initial state energy) of the entire process of lithium ion migration from the shell surface to the core layer positive electrode material. Among them, the final state energy and the initial state energy are the energies of the system structure after lithium ions are embedded in and not embedded in the positive electrode material, respectively, which can be obtained by DFT calculation of the corresponding system structure. The transition state can be obtained by the Nudged elastic band (NEB) method. Then, based on the Arrhenius formula: r = A”exp(-E a / kT) to calculate the lithium ion migration rate r of different coating materials; where A” is the leading factor, E a is the migration energy barrier, k is the Boltzmann constant, and T is the temperature. LiNbO3 materials with a migration barrier lower than 0.4 eV are selected as the migration system of the coating material.
[0064] ⑤ In the database of the formation energy system of the selected coating materials, the interfacial electrolyte reaction is studied. The reaction activity of different coating materials with the electrolyte and solvent of the pre-assembled battery system is calculated, including the reaction thermodynamic changes and energy barrier changes, and the coating material LiNbO3, which is inert to the electrolyte reaction of the pre-assembled battery system, is selected as the reaction kinetic system of the coating material.
[0065] ⑥ From the migration system of the coating material in step ④ and the reaction kinetic system of the coating material in step ⑤, screen out the coating material that satisfies both the migration system of the coating material and the reaction kinetic system of the coating material, namely, LiNbO3 material, as the best coating material for the NCM811 positive electrode.
[0066] An electrode material, wherein the screened LiNbO3 coating material and NCM811 positive electrode material are made into a core-shell structure composite electrode material, and the preparation method thereof is as follows:
[0067] ① Take 0.8 mol / L of 1 mol / L NiSO4·6H2O, 0.1 mol / L of CoSO4·7H2O, and 0.1 mol / L of MnSO4·H2O (Ni:Co:Mn=8:1:1) and mix them evenly. Add 5 mol / L NaOH solution and 4 mol / L NH3·H2O solution to the reaction tank, adjust the pH value to 10, and perform coprecipitation reaction. After washing with water, filtering and drying, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 precursor.
[0068] ②Using the molar ratio of Li: (Ni+Co+Mn) = 1:1, the lithium source and Ni0.9Co0.05Mn0.05(OH)2 precursor were uniformly mixed in a mixing tank for 10 hours, and then sintered in two stages under oxygen. First, pre-heat at 500℃ for 5-10 hours, and then sintered at 800℃ for 15 hours. After naturally cooling to 90℃, the sample was taken out to obtain the ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811).
[0069] ③ Weigh 0.6g Nb2O5 and 110g nickel-cobalt-manganese oxide precursor, disperse them into 100g of ethanol and water mixture (ethanol: water = 5:1), transfer to an oil bath and stir, set the stirring speed to 300rpm, and the temperature to 90℃. Wait for the mixture to evaporate to dryness, place the product in a sagger, transfer to a box furnace, adjust the heating rate to 10℃ / min, and place it for 8 hours after reaching 500℃. After that, cool it naturally to room temperature to obtain a lithium niobate-coated ternary positive electrode material, namely NCM811 / LiNbO3 composite positive electrode material.
[0070] A lithium ion battery, the assembly steps of which include:
[0071] Weigh 0.5g of lithium niobate coated nickel cobalt manganese NCM811 ternary positive electrode material NCM811 / LiNbO3, 0.1g of carbon black conductive agent, and 0.1g of polyvinylidene fluoride binder, and evenly coat them on copper foil to obtain a positive electrode sheet. The separator is a PE film, the counter electrode is a lithium metal sheet, the electrolyte is 1M LiPF6 / (EC:DMC=1:1), and a button cell is assembled in an inert gas glove box to obtain a lithium ion battery.
[0072] Comparative Example 1
[0073] A lithium-ion battery, the preparation of which includes the steps of weighing 0.5g of nickel-cobalt-manganese NCM811 ternary positive electrode material, 0.1g of carbon black conductive agent, and 0.1g of polyvinylidene fluoride binder, and uniformly coating them on copper foil to obtain a positive electrode sheet. The separator is a PE film, the counter electrode is a lithium metal sheet, the electrolyte is 1M LiPF6 / (EC:DMC=1:1), and the button cells are assembled in an inert gas glove box to obtain a lithium-ion battery.
[0074] Comparative Example 2
[0075] A lithium-ion battery, the preparation of which includes the steps of weighing 0.5g of lithium phosphate-coated nickel-cobalt-manganese NCM811 / Li3PO4 composite ternary positive electrode material, 0.1g of carbon black conductive agent, and 0.1g of polyvinylidene fluoride binder, and uniformly coating them on copper foil to obtain a positive electrode sheet. The diaphragm is a PE film, the counter electrode is a lithium metal sheet, the electrolyte is 1M LiPF6 / (EC:DMC=1:1), and the button cells are assembled in an inert gas glove box to obtain a lithium-ion battery.
[0076] Further, in order to verify the progress of the embodiments of the present application, the lithium ion batteries prepared in Example 1 and Comparative Example 1 were subjected to cycle charge and discharge performance tests in the voltage range of 2 to 4.2 V and at a rate of 0.1 C. The test results are shown in Table 1 below:
[0077] Table 1
[0078]
[0079] It can be seen from the above test results that the NCM811 / LiNbO3 composite positive electrode material obtained after screening the coating material by the electrode coating material screening method of Example 1 of the present application shows a greater advantage in terms of cycle stability when assembled with the lithium-ion battery, while the lithium-ion battery assembled with the uncoated NCM811 positive electrode in Example 1 and the lithium-ion battery assembled with the NCM811 composite positive electrode coated with Li3PO4 without screening in Example 2 show a significant decrease in capacity retention and poor cycle stability.
[0080] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for screening electrode coating materials, characterized in that: The following steps are involved: Obtaining an electrode active material, calculating the surface energy of different crystal faces of the electrode active material by density functional theory, and determining the interface structure of the electrode active material; Obtaining a coating material, calculating the surface energy of the coating material by density functional theory, and determining an interface system of the coating material; Based on the interface structure of the electrode active material and the interface system of the coating material, calculating the formation energy of the electrode active material and the coating material, and determining the formation energy system of the coating material; Based on the formation energy system of the coating material, the migration rate of lithium ions is calculated by density functional theory to determine the migration system of the coating material; Based on the formation energy system of the coating material, the reaction barrier and reaction thermodynamics of the coating material and the electrolyte are calculated by density functional theory to determine the reaction kinetic system of the coating material; Based on the migration system of the coating material and the reaction kinetics system of the coating material, the electrode coating material is screened and obtained.
2. The method for screening electrode coating materials according to claim 1, characterized in that: The step of calculating the surface energy of different crystal faces of the electrode active material comprises: performing a sectioning process on the electrode active material to construct different crystal faces, and calculating the surface energy of different crystal faces by the formula: γ1 = (E slab -NE bulk ) / 2A calculates the surface energy γ1 of different crystal planes; where E slab is the surface system energy of the electrode active material, E bulk is the bulk structure energy of the electrode active material, N is the number of atoms in the surface system of the electrode active material, and A is the surface area of the surface system of the electrode active material; And / or, the step of determining the interface structure of the electrode active material comprises: screening the surface energy below 0.5 The crystal plane serves as the interface structure of the electrode active material.
3. The method for screening electrode coating materials according to claim 1 or 2, characterized in that: The step of calculating the surface energy of the coating material comprises: obtaining different coating materials and performing cross-section processing, and calculating the surface energy of the coating material by the formula: γ2 = (E' slab -N'.E' bulk ) / 2A' to calculate the surface energy γ2 of different coating materials; where E' slab is the surface system energy of the coating material, E' bulk is the bulk structure energy of the coating material, N' is the number of atoms in the coating material surface system, and A' is the surface area of the coating material surface system; And / or, the step of determining the interface system of the coating material comprises: screening the surface energy of the coating material below 0.5 The coating material serves as the interface system of the coating material.
4. The method for screening electrode coating materials according to claim 3, characterized in that: The step of calculating the formation energy of the electrode active material and the coating material comprises: selecting the electrode active material and the coating material based on the interface structure of the electrode active material and the interface system of the coating material, and calculating the formation energy of the electrode active material and the coating material by the formula: f =E(Electrode|shell)-E(Electrode)-E(shell) Calculate the structure formation energy E between the selected electrode active material and the coating material f ; Wherein, E(Electrode|shell) is the surface system energy of the core-shell structure formed by the electrode active material and the coating material, E(Electrode) is the surface system energy of the electrode active material forming the electrode, and E(shell) is the surface system energy of the coating material forming the shell layer; And / or, the step of determining the formation energy system of the coating material includes: screening coating materials with surface formation energy lower than 0.8 eV as the formation energy system of the coating material.
5. The method for screening electrode coating materials according to claim 1 or 4, characterized in that: The step of calculating the lithium ion migration rate comprises: selecting a coating material from the formation energy system of the coating material, and calculating the lithium ion migration rate by the formula: a =E 过渡态 -E 初始态 Calculate the migration energy barrier E of lithium ions from the shell layer of the coating material to the core of the active material a , where E 过渡态 is the transition state structural energy, E 初始态 The architectural energy for lithium ions not embedded in active materials; By formula: r = A" exp (-E a / kT) to calculate the lithium ion migration rate r; where A” is the pre-factor, E a is the migration energy barrier, k is the Boltzmann constant, and T is the temperature; And / or, the step of determining the migration system of the coating material includes: screening a coating material with a lithium ion migration barrier not higher than 0.4 eV as the migration system of the coating material.
6. The method for screening electrode coating materials according to claim 5, characterized in that: The step of determining the reaction kinetic system of the coating material comprises: selecting a coating material having a reaction barrier with an electrolyte of not less than 0.7 eV and a thermodynamic reaction with the electrolyte of greater than 0 eV as the reaction kinetic system of the coating material; And / or, the step of screening the electrode coating material includes: selecting a coating material that satisfies both the migration system of the coating material and the reaction kinetics system of the coating material as the electrode coating material.
7. The method for screening electrode coating materials according to claim 1, characterized in that: The electrode active material is selected from positive electrode active materials, and the coating material is selected from positive electrode coating materials; Alternatively, the electrode active material is selected from negative electrode active materials, and the coating material is selected from negative electrode coating materials.
8. The method for screening electrode coating materials according to claim 7, characterized in that: The positive electrode active material is selected from at least one of: nickel cobalt lithium manganese oxide ternary material, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, and nickel cobalt aluminum oxide; The positive electrode coating material includes at least one of LiTaO3, Li3PO4, LiNbO3, Li2TiO2, Li2ZrO3, and Li2SiO3.
